Innovative Combined Truss: Experimental and Numerical Research - Gogol, Myron; Galinska, Tatyana; Kropyvnytska, Tatyana (International Journal of Engineering and Technology, 2018)
In the article, based on the analysis of modern trends in the development of construction in the world shown, that the problem of increasing the competitiveness and efficiency of building steel structures is relevant. Conducted research of steel combined structures confirmed, one of the effective methods for solving this problem is the use of a calculated method for regulating the stress deformation state (SDS) in steel metal structures during the design process. It does not require any additional material costs and allows you to design equally stressed structures as the most rational systems. The results of experimental research of a metal-wooden truss12 m spans with the calculated SDS regulation during the design process are presented. Experiment results data, reflecting the real work of a metal-wooden truss, satisfactorily agree with the theoretical. Experimental studies confirmed the hypothesis of the possibility of regulating the stress deformation state of combined structures with elastic-supportive supports and the achievement of an stress equality state in the calculated sections. A numerical experiment was conducted for a combined steel sprengel truss with a span of18 m. Rationalized, in terms of material costs, height of a sprengel truss, the angles of inclination of the compressed rods of the grating of the truss and the strength of the reinforcement system. Examples of implementation of such rational structures are given.Â Â